Challenges, barriers and coping strategies experienced by women leaders in public universities of Malaysia - Islam, Md Asadul (2019)
There are more female academicians than there are male working in the public universities of Malaysia; however, their representation in the administrative leadership positions is less than that of the men. This is a similar situation to that of public universities in many other countries. The lack of representation of women in the leadership positions in the higher institutions, such as public universities, is largely due to the challenges that are faced by them. This study explores these challenges that are preventing women in accessing and holding administrative leadership positions in Malaysian public universities, as well as investigating the challenges that may have a negative impact. Furthermore, the study explored strategies and actions that could be utilised in overcoming these challenges that women are facing. A qualitative approach, using explorative research design, was deemed appropriate for this study. The empirical study included twelve semi-structured interviews with female deans at six public universities in Selangor in Malaysia to explore the challenges faced by women. These challenges were categorised into three main types, which includes social, organisational and individual challenges. The study identified religion, male domination and negative attitudes of local people towards women leaders as the social challenges faced by women in accessing university leadership positions. However, among these challenges, only the negative attitudes of people in society exists for women who are already holding administrative leadership positions in public universities. However, this study finds internal politics, male domination, lack of benefits (both financial and non-financial) and biasness of top management personnel as the organisational challenges faced by women in accessing administrative leadership positions. However, subsequent organisational challenges are similar to the organisational challenges identified in accessing positions but the negative perception of colleagues and their lack of support, together with lack of childcare facilities, have also emerged as challenges for women who are already holding administrative leadership positions in the public universities of Malaysia. Furthermore, as far as individual challenges are concerned in accessing administrative leadership positions in the public universities, this study has identified familial responsibilities and a lack of motivation, technological knowledge, confidence and time management. However, only family responsibilities and lack of technological knowledge were found as the subsequent individual challenges for women holding the administrative leadership positions. Apart from these challenges, the study also attempted to identify some specific challenges highlighted by respondents that may have a negative impact on potential female leaders in Malaysian public universities. The study found that there were too many responsibilities for potential female leaders in universities, which was creating a negative impact, including difficulties in managing people, complicated promotion criteria, negative perceptions of colleagues and lack of financial benefits. The study finally concluded with some recommendations as coping strategies and actions derived from participants that could be utilised in overcoming the challenges faced by women in accessing and holding administrative leadership positions in Malaysian public universities. These included reducing responsibilities, training, organising seminars, symposiums and developing family friendly workplace facilities.